Competitiveness and Policy Analysis of Num-Mango in Vinh Long, Vietnam - Kiet Hong Vo Tuan Truong; Thien Chi Ngo; Dang Vo Gia Le; Truc Thanh Bao; Lan Thanh Kim Nguyen; Duc Huynh Lam; Hung Vu Nguyen; Son Hoang Tran (Migration Letters, 2023)
The influence of macroeconomic policy changes on the Num-mango supply chain is evaluated via the use of the policy analysis matrix. The study included the evaluation of 317 data points obtained from the primary participants and sponsors of the chain. Examples of global macroeconomic policies that have a substantial influence on the economic efficiency and competitiveness of export channels include safeguarding production prices, managing currency rates, and providing local cost subsidies. The results indicate that the domestic channel 4 (with a PRC value below one) exhibits competitiveness, whereas export channels 1, 2, and 3 (with PRC values below one, DRC values below one, and SBC values above one) possess both comparative and competitive advantages. The government demonstrates a preference for export channel 1, as shown by its emphasis on safeguarding production (NPCO 0.18 and EPC 0.16) and enhancing value via additional measures (SRP -0.22). The channel 4 is the second priority from government with subsidy policy of tradable inputs cost compared to the channels 2 and 3 (NPCI 0.63). The export channels 2 and 3 are promoted export by added value increase policy (EPC 0.69 and 0.58). When there is a 20% variation in the tradable cost, the ratio between sensitivity analysis’s SBC to EPC to SRP also changes. Another notable element is that although the DRC and SBC see a 20% reduction in domestic costs, the EPC remains untouched by this change. A reduction of 20% in both domestic cost and tradable cost, coupled with a corresponding gain of 20% in the Free on Board (FOB) price, led to a notable enhancement in the SRP for export channels 1, 2, and 3. The suggested retail price is mostly influenced by domestic expenditures.